Oculomotor nerve palsy secondary to aberrant posterior cerebral artery - Tan, Terence (BMJ Publishing Group, 2014)
The authors report a rare case of an oculomotor nerve palsy attributed to mass effect from an aberrant posterior cerebral artery. The patient presented with complete ptosis, mydriasis and ophthalmoplegia of the affected eye. MRI demonstrated distortion of the oculomotor nerve as it traversed inferior to the non-aneurysmal P1 segment of an aberrant posterior cerebral artery. The oculomotor nerve palsy resolved spontaneously.